Implementasi Strategi Keuangan dan Dampaknya terhadap Profitabilitas: Studi Kasus PT Fast Food Indonesia Tbk - Aslam, Annisa Paramaswary; Anwar; Syardiansyah; Taufik, Anisya Devinta; Amalia, Regina; Ayu, Dian Fajar (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to analyze the financial performance and adaptive strategies of PT Fast Food Indonesia Tbk (KFC Indonesia) in facing significant business pressures and economic challenges during the 2023–2024 period. The decline in sales, boycotts of U.S. products, rising operational costs, and intense competition from SMEs are key external factors that have worsened the company’s financial performance. Nevertheless, the company still demonstrates efficiency in inventory turnover and holds a strong brand presence. The short-term and long-term strategies implemented include operational efficiency, product innovation tailored to local tastes, digital transformation through the development of the KFCku app, as well as optimizing communication and customer experience. The study concludes that the company's success in overcoming the crisis depends on strengthening its financial structure, accelerating digitalization, consumer-based innovation, and adaptive strategies to navigate a competitive market dynamic.